Study related factors associated with study engagement and student burnout among German university students - Olson, Nils; Oberhoffer-Fritz, Renate; Reiner, Barbara; Schulz, Thorsten (Frontiers in Public Health, 2023)
Introduction Student burnout has become a health concern in higher education systems. Its prevalence rates are high due to specific demands in this life situation. It leads not only to increased academic dropout rates but is also associated with negative health outcomes both physically and mentally. Its counterpart is study engagement, which is a positive, fulfilling, study-related attitude characterized by energy, dedication, and absorption. There has not been a systematical approach covering the demands directly posed by the academic environment itself. Additionally, academic subject fields apart from medicine and nursing sciences have been mostly neglected in regards to this research field. The aim of the study is therefore to identify contributing factors for both burnout and engagement within the academic environment in a sample of different subject fields at a German university. Methods In a cross-sectional study, a sample of 3,451 students of all academic subjects at a technical university in Germany has been analyzed using an online survey. Sociodemographic data, study engagement, student burnout, study satisfaction, academic workload, number of semesters and occupational liabilities have been analyzed. Binary logistic regression was used to determine the associations of burnout symptoms and study engagement. Results Almost a third of the students showed frequent burnout symptoms, while 42.5% showed a high degree of study engagement with no differences in gender. Age was identified as a risk factor for frequent signs of cynicism (OR = 1.073). Study satisfaction (OR between 0.459 and 0.702), semester progression (OR = 0.959) and working moderately (OR between 0.605 and 0.637) was associated with fewer symptoms in different burnout-dimensions. Study satisfaction is positively associated with study engagement (OR = 2.676). Academic workload is positively related to both burnout (OR between 1.014 and 1.021) and study engagement (OR = 1.014). Discussion A substantial number of students show frequent symptoms of burnout and the majority is not highly engaged. The included factors contribute to the model to various degrees and show that university-bound factors play a major role. Fostering a supportive environment is key for study engagement, health and well-being. The inclusion of further, individual factors should be a future concern in order to find and promote strategies for a healthy education system.